Acute citrulline-malate ingestion does not enhance performance in judo athletes - Biccas Viana, J. C.; Persio Azevedo, A.; Freire de Almeida, R.; Vicentini, G.; Garrone Barauna, V.; Guimaraes-Ferreira, L. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2021)
Background. Judo is a combat sport that involves grappling and throwing techniques, and multiple high-intensity efforts. Citrul-line Malate (CM) is a nutritional supplement used to enhance physical performance, albeit not all studies have corroborated its ergogenic properties during high-intensity exercise.Problem and aim. To the best of our knowledge, the effects of CM on judo performance has not been investigated. To fill this gap the aim of the current study was to investigate the effects of acute CM ingestion on performance in judo athletes.Methods. Using a randomized crossover and double-blinded design, 10 judo athletes ingested 8g of CM (2:1 proportion) or pla-cebo 60 minutes prior to the execution of three bouts of the Special Judo Fitness Test (SJFT). The number of throws, the SJFT index, blood lactate concentration before and after each bout and rating of perceived exertion (RPE) after each bout were assessed. Results. Acute CM ingestion did not result in an increase of throws during three sets of the SJFT, nor in the SJFT index and RPE. The blood lactate concentration was higher in the CM condition only after the second SJFT bout, with no differences at any other time points.Conclusions. Acute CM ingestion by judo athletes did not improve performance in the SJFT.